Odpowiedź :
a) x+x+x+x+x dla x= -2
5x
-2*5= -10
b) x+y+y+z+x+z+x+z+x dla x= 3, y= 2, z= 1
4x+2y+3z
4*3+2*2+3*1=12+4+3=19
c) a+b+2c+2a+3b+4b+3a+3c dla a= 0.5, b= 4, c=0.1
6a+8b+5c
6*0,5+8*4+0,1*5=3+32+0,5=35,5
d)4x+2y+2-3z-2x+3y+7z+4 dla x=½ y= ⅕ z=¼
2x+5y+4z+4
2*0,5+5*1/5+4*1/4+4=1+1+1+4=7
5x
-2*5= -10
b) x+y+y+z+x+z+x+z+x dla x= 3, y= 2, z= 1
4x+2y+3z
4*3+2*2+3*1=12+4+3=19
c) a+b+2c+2a+3b+4b+3a+3c dla a= 0.5, b= 4, c=0.1
6a+8b+5c
6*0,5+8*4+0,1*5=3+32+0,5=35,5
d)4x+2y+2-3z-2x+3y+7z+4 dla x=½ y= ⅕ z=¼
2x+5y+4z+4
2*0,5+5*1/5+4*1/4+4=1+1+1+4=7
a) x+x+x+x+x dla x= -2
5x = 5*(-2 ) = -10
b) x+y+y+z+x+z+x+z+x dla x= 3, y= 2, z= 1
4x + 2y + 3z = 4*3 + 2*2 + 3*1 = 12 + 4 + 3 = 19
c) a+b+2c+2a+3b+4b+3a+3c dla a= 0.5, b= 4, c=0.1
6a + 8b + 5c = 6*0,5 + 8*4 + 5*0,1 = 3 + 32 + 0,5 = 35,5
d)4x++2y+2-3z-2x+3y+7z+4 dla x=½ y= ⅕ z=¼
2x +5y + 4z +6 = 2*½ + 5*(1/6) + 4*¼ +6 = 1 + 5/6 + 1 +6 =
= 8 + 5/6 = 9i 1/6
5x = 5*(-2 ) = -10
b) x+y+y+z+x+z+x+z+x dla x= 3, y= 2, z= 1
4x + 2y + 3z = 4*3 + 2*2 + 3*1 = 12 + 4 + 3 = 19
c) a+b+2c+2a+3b+4b+3a+3c dla a= 0.5, b= 4, c=0.1
6a + 8b + 5c = 6*0,5 + 8*4 + 5*0,1 = 3 + 32 + 0,5 = 35,5
d)4x++2y+2-3z-2x+3y+7z+4 dla x=½ y= ⅕ z=¼
2x +5y + 4z +6 = 2*½ + 5*(1/6) + 4*¼ +6 = 1 + 5/6 + 1 +6 =
= 8 + 5/6 = 9i 1/6